2018
DOI: 10.18632/oncotarget.25803
|View full text |Cite
|
Sign up to set email alerts
|

Palbociclib resistance confers dependence on an FGFR-MAP kinase-mTOR-driven pathway inKRAS-mutant non-small cell lung cancer

Abstract: CDK4 is emerging as a target in KRAS-mutant non-small cell lung cancer (NSCLC). We demonstrate that KRAS-mutant NSCLC cell lines are initially sensitive to the CDK4/6 inhibitor palbociclib, but readily acquire resistance associated with increased expression of CDK6, D-type cyclins and cyclin E. Resistant cells also demonstrated increased ERK1/2 activity and sensitivity to MEK and ERK inhibitors. Moreover, MEK inhibition reduced the expression and activity of cell cycle proteins mediating palbociclib resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 51 publications
6
43
0
Order By: Relevance
“…It now appears that in many tumor contexts, there exist parallel or adaptive pathways that allow for cell cycle progression in spite of pharmacological CDK4/6 inhibition ( Figure 2). Multiple studies over the last year have begun to shed-light on this "dark-side" of the cell cycle, where other CDK complexes compensate for the pharmaceutical suppression of CDK4/6 and limit therapeutic efficacy [31][32][33][34]. These finding are congruent with prior observations indicating cells can divide in the genetic absence of CDK4 and 6 activity and clearly illustrate the involvement of compensatory pathways [35].…”
Section: Cell Cycle Plasticity and Enhancing Depth Of Cell Cycle Exitsupporting
confidence: 75%
“…It now appears that in many tumor contexts, there exist parallel or adaptive pathways that allow for cell cycle progression in spite of pharmacological CDK4/6 inhibition ( Figure 2). Multiple studies over the last year have begun to shed-light on this "dark-side" of the cell cycle, where other CDK complexes compensate for the pharmaceutical suppression of CDK4/6 and limit therapeutic efficacy [31][32][33][34]. These finding are congruent with prior observations indicating cells can divide in the genetic absence of CDK4 and 6 activity and clearly illustrate the involvement of compensatory pathways [35].…”
Section: Cell Cycle Plasticity and Enhancing Depth Of Cell Cycle Exitsupporting
confidence: 75%
“…These data showed that CDK4/6 inhibition had no effect related to canonical signaling through ERK, AKT, or MTOR pathways as determined by phosphorylation of ERK, AKT and S6 respectively (Fig S1). However, the treatment with trametinib resulted in expected suppression of ERK activity and in several models also suppressed activity through the MTOR and AKT pathways (Fig S1), as has been recently reported in other RAS-driven tumors 17 . To determine the features of therapeutic cooperation, we interrogated canonical determinants of cell cycle control.…”
Section: Resultssupporting
confidence: 79%
“…Interestingly, in preclinical studies PDAC models are surprisingly resistant to CDK4/6 inhibition 14, 15 . However, combination with MTOR or MEK inhibitors have been reported to enhance response to CDK4/6 inhibition in PDAC and other RAS-driven tumor types 15-17 . In spite of the potency of such combinations in enforcing cell cycle withdrawal, tumor cells continue to survive and as a result acquired resistance represents a significant challenge with such cytostatic combinations.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the CDK4/cyclin D-Rb axis on cell size regulation has been purported by studies from our lab and others (Ginzberg et al, 2018;Schmoller et al, 2015;. While the mechanisms by which CDK4 activity sets target size remains to be investigated, there is increasing evidence that inhibition of CDK4 activity results in increased biosynthetic capacity, such as mitochondrial size and activity, presumably through its feedback on mTORC1 signaling (Cretella et al, 2018;Franco et al, 2016;Haines et al, 2018;Jansen et al, 2017;Romero-Pozuelo et al, 2020).…”
Section: Discussionmentioning
confidence: 91%